2001
DOI: 10.1067/mva.2001.118808
|View full text |Cite
|
Sign up to set email alerts
|

Transluminal placement of endovascular stent-grafts for the treatment of type A aortic dissection with an entry tear in the descending thoracic aorta

Abstract: Stent-graft repair of aortic dissection with an entry tear in the descending thoracic aorta is a safe and effective method and may be an alternative to surgical graft replacement in highly selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
71
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(72 citation statements)
references
References 18 publications
1
71
0
Order By: Relevance
“…Kato et al 21 reported successful stent-graft repair of type A AD with an entry in the descending thoracic aorta. Ishihara et al 22 reported successful one-stage repair of the dissected aorta by interpolating a synthetic graft with a self-expandable stent with only a median sternotomy.…”
Section: Ii-303mentioning
confidence: 99%
“…Kato et al 21 reported successful stent-graft repair of type A AD with an entry in the descending thoracic aorta. Ishihara et al 22 reported successful one-stage repair of the dissected aorta by interpolating a synthetic graft with a self-expandable stent with only a median sternotomy.…”
Section: Ii-303mentioning
confidence: 99%
“…(13) It has also been proposed that early medical optimisation with controlled use of definitive surgery may be (3) Some authors have suggested that medical therapy may be complimented by early endovascular stenting as an alternative to emergency surgery in selected cases, when there is no evidence of early complication. (14) In summary, the ability to provide early, accurate diagnosis and characterisation for patients with acute aortic dissection is improving, due to earlier access to advanced imaging while patients are still within the emergency department. Radiologists, and residents in particular, should be aware of a lesser-described entity: a retrograde Stanford Type A aortic dissection originating in the descending thoracic aorta.…”
Section: Discussionmentioning
confidence: 99%
“…Reports on handmade SGs are limited, and the results in these cases are unknown. [15][16][17][18][19][20][21][22][23] In Japan, EVR devices have not been approved as medical devices thus far. Therefore some medical institutions produce their own handmade SGs, and compared with other countries, only a small number of patients undergo this procedure in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, both the materials used to prepare the SGs and the procedure followed for EVR vary, and the clinical results are influenced by the institutional indications and techniques. 1,[16][17][18][19][20] Our department has been producing and using SGs that comprise stainless steel Z stents and are covered with an ultrathin-wall woven polyester fabric. The initial and midterm results for repair using these handmade SGs for thoracic and abdominal aortic diseases in high-risk patients are considered to be satisfactory.…”
Section: Discussionmentioning
confidence: 99%